Presence of Any Medical Debt Associated With Two Additional Years of Homelessness in a Seattle Sample - Jessica E. Bielenberg MPH; Marvin Futrell; Bert Stover PhD; Amy Hagopian PhD (SAGE Publishing, 2020)
Although medical debt has been associated with housing instability, almost no research has connected homelessness to medical debt. We interviewed 60 individuals experiencing homelessness in Seattle, selected from those participating in self-governed encampments organized by a homeless advocacy organization. Most respondents reported having at least one kind of debt, with two-thirds reporting current medical debt. Almost half reported trouble paying medical bills for themselves or family members. Almost one-third believed medical debt was in part responsible for their current housing situation. More than half with medical debt incurred this debt while they were covered under insurance. People who had trouble paying medical bills experienced a more recent episode of homelessness 2 years longer than those who did not have such trouble, even after controlling for race, education, age, gender, and health status. People of color who had trouble paying medical bills reported almost 1 year more homelessness than whites.